Association between Tea Consumption and Hypertension Risk among Middle-Aged and Older Chinese Adults. Issue 12 (29th September 2021) - Feng, Chengwu; Cao, Yaying; Su, Yang; Cai, Hui; Shu, Xiao-Ou; Zheng, Wei; Yu, Danxia; Zong, Geng
ABSTRACT: Background: Current evidence on tea consumption and hypertension is inconclusive, and prospective studies among habitual tea drinkers remain limited. Objective: We investigated the associations of habitual tea consumption with hypertension risk and longitudinal blood pressure changes in 2 large cohorts. Methods: This study included participants aged 40–75 y from the Shanghai Women's Health Study ( n = 31, 351) and the Shanghai Men's Health Study ( n = 28, 342), without hypertension, diabetes, cardiovascular disease, or cancer at baseline. Information on tea consumption was assessed during in-person interviews at enrollment and follow-up visits. Incident hypertension was identified by self-reported diagnosis, medication use, or blood pressure measurements. Results: Current tea drinkers had a 7% higher risk than the non–current tea drinker group [HRs (95% CIs): women, 1.07 (1.01, 1.14); men, 1.07 (1.02, 1.12)]. The amount of tea drinking showed significant dose–response associations with hypertension: compared with the non-current group, HRs (95% CIs) for women and men were 1.01 (0.90, 1.14) and 1.02 (0.96, 1.08) for low (women/men: <100/200 g/mo), 1.07 (1.01, 1.15) and 1.05 (0.99, 1.12) for medium (women/men: 100–250/200–250 g/mo), and 1.18 (1.01, 1.39) and 1.10 (1.03, 1.17) for the high-amount group (women/men: >250 g/mo). Among participants without hypertension, compared with non–current tea drinkers, least-squares means of 3-y changes in blood pressure were 0.3–0.4 mm Hg higher for women and men as current drinkers and 0.7–0.9 mm Hg higher for men in the high-consumption group. Compared with those who never drank tea, women who drank tea consistently had 0.5 (0.2, 0.7) mm Hg higher diastolic blood pressure (DBP), whereas men had 0.5 (0.04, 0.9) mm Hg higher systolic blood pressure and 0.3 (0.04, 0.6) mm Hg higher DBP, respectively. Conclusions: Our findings suggest that habitual tea drinking is associated with a slightly higher risk of hypertension and a minor increase in blood pressure among middle-aged and older Chinese adults, which warrants confirmation by long-term intervention studies.